Juridical Analysis Of The Effectiveness Of The Implementation Of Military Police Duties In Maintaining Order And Discipline Of Military Members. Discipline Of Military Members (Research Study On Military Police Detachment I/6 Batam) - Stevanus Purba; Soerya Respationo; Lagat Parroha Patar Siadari (Journal of Innovative and Creativity, 2025)
The Military Police serve as the internal law enforcement within the Indonesian National Armed Forces (TNI), strategically maintaining order and discipline among soldiers as part of the military justice system. The increasing issue of disciplinary violations within the military environment, especially in strategic areas such as Batam, presents a real challenge for the Military Police Detachment I/6 Batam in carrying out its duties. This study aims to analyse, from a legal perspective, the legal regulations, the effectiveness of task implementation, and the obstacles and solutions that can be applied to enforce military discipline. This research employs normative and empirical juridical approaches. Primary data were obtained through direct interviews with PM officers, field observations, and internal document studies, while secondary data were sourced from legislative regulations such as Law No. 34 of 2004, Law No. 25 of 2014, and the Military Criminal Code. The analysis used supervisory theory, legal system theory, and the theory of legal certainty as analytical tools. The research results show that, normatively, the legal basis for the role of the Military Police is already quite strong; however, in practice, the effectiveness of task implementation still faces internal obstacles such as limited personnel, operational facilities, and training, as well as external obstacles in the form of the influence of social dynamics, civil-military interactions, and weak inter-agency coordination. Enhancement efforts are being made through strengthening technology-based supervision systems, technical training, reinforcing military ethical values through daily orders from the Commander of the Indonesian National Armed Forces (TNI), and cross-agency synergy. It is recommended that the TNI institution and the government provide greater support in the form of policies, budgeting, and structured training to improve the effectiveness of the Military Police as disciplined law enforcers within a professional and dignified military body.